The advertisement call and geographic distribution of Proceratophrys dibernardoi Brandão, Caramaschi, Vaz-Silva & Campos 2013 (Anura, Odontophrynidae) - Ferreira, Cláudia Márcia Marily; Sugai, José Luiz Massao Moreira; de Souza, Franco Leandro; de Andrade, Sheila Pereira; Vaz-Silva, Wilian; Bastos, Rogério Pereira; de Morais, Alessandro Ribeiro (Zootaxa, 2016)
Proceratophrys dibernardoi Brandão, Caramaschi, Vaz-Silva & Campos 2013 has recently been described and allocated into the P. cristiceps species group, but no information about its advertisement calls has been provided (Brandão et al. 2013). Here, we describe for the first time the advertisement calls of P. dibernardoi based on specimens from Central Brazil. We also expand P. dibernardoi´s geographic distribution by reporting a new population in the State of Mato Grosso do Sul, Brazil, constituting the westernmost record for this species, and extending its known range approximately 330 km westward of the municipality of Aporé, State of Goiás (P. dibernardoi´s former westernmost record).